Global Literature Trend on Collaborative Governance (Scientometric Analysis in the Social Sciences Discipline) - Mashur, Dadang; Mayarni, Mayarni; Handoko, Tito; Rafi, M (SCAD Independent, 2023)
Collaborative governance (CG) is a framework considered appropriate for every entity, especially the government, to overcome various problems in public services that feel suffocating. CG grows yearly; various empirical and theoretical perspectives have been discussed, but some still need to highlight their various terms. Therefore, this paper aimed to map collaborative governance research, particularly social science. The Scopus database was used for literature, and 386 articles were yielded. Furthermore, the VOSViewer is software to visualize thematic data synthesis. This study found a significant evolution during two decades in CG studies and reported several essential issues. Ansell, C., published the most articles, Meijer & Bolvar (2016) received the most citations, and Ansell, C. and Torfing, J were the authors with the most active collaborative networks. Additionally, Roskilde Universitet was the top affiliation that published their work. The USA had a robust international research collaboration network, and Sustainability Switzerland published the most papers for CG’s study). Likewise, the most frequent co-occurrences of keywords were “collaborative governance”, “governance approach”, “water Management”, “stakeholders”, “decision making”, and “participatory approach”. Another point, there were the top five most distinguished themes selected; “food security”, “smart city”, “technology